Konstruksi Sosial Transgender di Kabupaten Jember Pasca Jember Fashion Carnival: Perspektif Hak Asasi Manusia - Muhammad Aenur Rosyid; Syamsul Anam (Badan Strategi Kebijakan Hukum, 2023)
The issue of discrimination and negative stigmatization of transgender people in the Jember Regency is considered an obstacle to the freedom of expression for every individual. This study aims to analyze the views of the people of the Jember Regency in regard to transgender women's right to freedom of expression after the Jember Fashion Carnival event. This research utilizes an empirical juridical research method with sociological approach and legal approaches. The results of this study indicate that the community's social construction of the rights of transgender expression after the Jember Fashion Carnival event is demonstrated through the community's appreciation of the transgender people's works at the event and the provision of space for their expression to develop creativity. Although the government of Jember Regency has not implemented specific policies to protect the rights of transgender people in expressing themselves and developing their potential, the government and residents of Jember have recognized the transgender community as citizens with equal rights and positions to express themselves and contribute to the progress of Jember Regency.